Proteomic Analysis of Plasma Membrane Proteins in an In Vitro Blood-Brain Barrier Model - Duban-Deweer, Sophie; Hachani, Johan; Deracinois, Barbara; Cecchelli, Roméo; Flahaut, Christophe; Karamanos, Yannis (IntechOpen, 2012)
None